1997
DOI: 10.1111/j.1525-1594.1997.tb00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutaraldehyde Treated Bovine Pericardium: Changes in Calcification Due to Vitamins and Platelet Inhibitors

Abstract: Cardiovascular calcification, the formation of calcium phosphate deposits in cardiovascular tissue, is a common endstage phenomenon affecting a wide variety of bioprostheses. The purpose of the present paper is to study the possibility that some antiplatelet drugs (aspirin and persantine) and certain vitamins (vitamin C, vitamin B,, and vitamin E) and their combinations might prevent the mineralization of glutaraldehyde treated bovine pericardium (GABP) by modifying the pericardial surface. In this experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Thus, the extraction of cellular components from BP tissues should minimize immunologically induced inflammatory processes and attenuate the calcification occurring as a late sequela of inflammatory [21,22]. Table 1 Calcium content, phosphorous content and Ca/P (molar ratio) of the different groups implanted 4 weeks, 6 The significant differences were found between the GFaBP group and the GFaBP-HA group after four, six and eight-week implantations. In fact, the calcium contents of GFaBP-HA group were about 10 times lower than those of the GFBP group after eight-week implantations (0.25±0.08 comparing to 2.44±0.55 ȝgCa/mg).…”
Section: In Vivo Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the extraction of cellular components from BP tissues should minimize immunologically induced inflammatory processes and attenuate the calcification occurring as a late sequela of inflammatory [21,22]. Table 1 Calcium content, phosphorous content and Ca/P (molar ratio) of the different groups implanted 4 weeks, 6 The significant differences were found between the GFaBP group and the GFaBP-HA group after four, six and eight-week implantations. In fact, the calcium contents of GFaBP-HA group were about 10 times lower than those of the GFBP group after eight-week implantations (0.25±0.08 comparing to 2.44±0.55 ȝgCa/mg).…”
Section: In Vivo Calcificationmentioning
confidence: 99%
“…Despite the clinical importance of the problem, the pathogenesis of calcification is incompletely understood. According to present studies, there are several currently accepted reasons resulting in calcification: (i) immunogenicity resulted from cells, cellular components and soluble proteins of xenogenic tissue may be the major factor contributing to the calcification [1]; (ii) lipid-based cell debris, in particular the acid phospholipids of cell membranes could serve as the initial nuclei of calcification [2]; (iii) incomplete glutaraldehyde binding to collagen also yields cytotoxic aldehyde group residuals including loosely bound glutaraldehyde and unreacted aldehyde groups, which could also induce calcification [3,4]; (iv) voids and cavities in the tissue, which were created by the removal of cellular components and proteoglycans during processing, cellular degradation, or chemical treatment, afford a potential space for calcium phosphate depositing [5]; and (v) certain medicines such as steroid hormones, antibiotic drugs, vitamins, antiplatelet drugs, anticoagulants, etc., can alter protein surface attachment and modulate the calcium transport and subsequent tissue calcification [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…According to Schoen et al [7,8], Chanda et al [21], Vasudev et al [22] and Pires et al [9] this calcification is a multifactorial phenomenon, but it is not well defined and varies in different animal models. The authors pointed out that calcification in bovine pericardium used as a vascular patch presented a different connotation of calcification than valvular prostheses, because it implied a reduction in leaflet mobility, resulting in dysfunction of the prosthesis, which was not observed in vascular grafts.…”
Section: Discussionmentioning
confidence: 99%
“…where vitamin C intake in postmenopausal women was stratified by calcium intake, it was found that all the increase in BMd was clustered among those with calcium intake >500mg/d while there was no association between vitamin C intake and BMd where calcium intake was lower 58 . leveille et al found that food-derived vitamin C was not associated with BMd in postmenopausal women but supplements for women aged [55][56][57][58][59][60][61][62][63][64] , but not older, used for ≥10 years showed a significantly higher BMD 68 .…”
Section: Calcificationmentioning
confidence: 99%
“…ascorbic acid may, often together with alpha-tocopherol, lower induced calcification in VSMCs 14,[60][61][62] , possibly by reducing transport of calcium ions 61 . In observational studies, however, intake of vitamin C was not associated with the CaC score in asymptomatic subjects 34 , while dietary and plasma vitamin C showed no association with cIMt or carotid plaque 35 .…”
Section: Calcificationmentioning
confidence: 99%